The Emerging Epigenetic Role of CD8+T Cells in Autoimmune Diseases: A Systematic Review - Deng, Qiancheng; Luo, Yangyang; Chang, Christopher; Wu, Haijing; Ding, Yan; Xiao, Rong (Frontiers in Immunology, 2019)
Autoimmune diseases are usually complex and multifactorial, characterized by aberrant production of autoreactive immune cells and/or autoantibodies against healthy cells and tissues. However, the pathogenesis of autoimmune diseases has not been clearly elucidated. The activation, differentiation, and development of CD8+ T cells can be affected by numerous inflammatory cytokines, transcription factors and chemokines. In recent years, epigenetic modifications have been shown to play an important role in the fate of CD8+ T cells. The discovery of these modifications that contribute to the activation or suppression of CD8+ cells has been concurrent with the increasing evidence that CD8+ T cells play a role in autoimmunity. These relationships have been studied in various autoimmune diseases, including multiple sclerosis (MS), systemic sclerosis (SSc), type 1 diabetes (T1D), Grave’s disease (GD), systemic lupus erythematosus (SLE), aplastic anemia (AA) and vitiligo. In each of these diseases, genes that play a role in the proliferation or activation of CD8+ T cells have been found to be affected by epigenetic modifications. Various cytokines, transcription factors, and other regulatory molecules have been found to be differentially methylated in CD8+ T cells in autoimmune diseases. These genes are involved in T cell regulation, including interferons, interleukin (IL)，tumor necrosis factor (TNF), as well as linker for activation of T cells (LAT), cytotoxic T-lymphocyte–associated antigen 4 (CTLA4), and adapter proteins. MiRNAs also play a role in the pathogenesis of these diseases and several known miRNAs that are involved in these diseases have also been shown to play a role in CD8+ regulation.